Study of Biodiesel Production through Esterification Catalysed by Imidazolium-based Ionic Liquids - Alimova, Irana (2017)
Biodiesel is an alternative diesel fuel which is industrially produced from vegetable oils and animal fats, by transesterification reactions. Thus, currently most commercial biodiesel is produced from oils, using alkaline catalysts. On the other hand, conventional mineral acid catalysts like sulfuric acid, are commonly used for catalyzing esterification reactions of fatty acids which also produce biodiesel. However, Ionic Liquids (ILs) offer an alternative solution to classical homogeneous catalysts, because it can be recycled and reused in subsequent runs after recovery steps. An IL is a molten salt consisting of a cation and an anion, with low melting temperature. In this study, a Brønsted acidic IL, 1-butyl-3-methylimidazolium hydrogen sulfate ([BMIM][HSO4]) was used as a catalyst in the esterification of oleic acid with methanol into biodiesel. The effect of different operation parameters such as oleic acid to methanol molar ratio, amount of catalyst, reaction temperature, and reaction time were tested. The optimal conditions for esterification of oleic acid were experimentally determined at 1/10 for oleic acid/methanol molar ratio, 2.5 %wt for the amount of catalyst, a reaction time of 4 h and reaction temperature of 90oC. The Fatty Acid Methyl Esters (FAMEs) content was analyzed using Gas Chromatography.